Sociopolitical activism in urban arts by Miguel Januário - Ribeiro, Roney Jesus; Mallagutti, Michele Marques da Silva (Revista do Colóquio, 2024)
This article aims to expand reflections on the sociopolitical engagement of the Portuguese artist Miguel Januário, who, through the “±MAISMENOS±” project, addressed the social and economic crisis in Portugal. The political activism adopted by the artist placed him among the greatest references of urban art in his country. In this study, we analyzed four works from the ‘±MAISMENOS±’ project, by Januario.